2003
DOI: 10.1176/appi.ajp.160.3.577
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cortical GABA Concentrations in Depressed Patients Receiving ECT

Abstract: Occipital cortex GABA concentrations increase two-fold following ECT. This suggests possible GABAergic involvement in ECT's mechanism of anticonvulsant and antidepressant actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
220
3
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 435 publications
(241 citation statements)
references
References 12 publications
10
220
3
8
Order By: Relevance
“…A proton magnetic resonance spectroscopy study in live patients shows a highly significant 52% reduction in GABA levels in the occipital cortex of 14 medication-free depressed subjects (Sanacora et al, 1999). Later studies by the same group demonstrate that low levels of GABA in the occipital cortex can be reversed by treatment with SSRIs or ECT (Sanacora et al, 2002(Sanacora et al, , 2003a. The ability of an SSRI to normalize GABA levels in depression and even increase it in healthy subjects (Bhagwagar et al, 2004b) suggests close interactions between these systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proton magnetic resonance spectroscopy study in live patients shows a highly significant 52% reduction in GABA levels in the occipital cortex of 14 medication-free depressed subjects (Sanacora et al, 1999). Later studies by the same group demonstrate that low levels of GABA in the occipital cortex can be reversed by treatment with SSRIs or ECT (Sanacora et al, 2002(Sanacora et al, , 2003a. The ability of an SSRI to normalize GABA levels in depression and even increase it in healthy subjects (Bhagwagar et al, 2004b) suggests close interactions between these systems.…”
Section: Discussionmentioning
confidence: 99%
“…A proton magnetic resonance spectroscopy study revealed a large, 52% reduction in GABA levels in the occipital cortex of 14 medication-free depressed subjects as compared to 18 healthy control subjects (Sanacora et al, 1999). Later studies by the same investigators demonstrated that low levels of GABA in the occipital cortex in depressed patients can be reversed by treatment with selective serotonin reuptake inhibitors (SSRIs) or ECT (Sanacora et al, 2002(Sanacora et al, , 2003a. Interestingly, in the occipital cortex of healthy controls, SSRI treatment also results in the acute elevation of GABA (Bhagwagar et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using proton magnetic resonance spectroscopy (MRS) have shown lowered GABA levels in occipital cortex in acutely depressed patients, particularly those with a melancholic syndrome (Sanacora et al 2004). Both SSRI treatment (Sanacora et al 2002) and electroconvulsive therapy (ECT) (Sanacora et al 2003) increase GABA levels in depressed patients ; however, this effect is not seen with cognitive behaviour therapy despite clinical improvement (Sanacora et al 2006).…”
Section: Gamma-aminobutyric Acid (Gaba)mentioning
confidence: 99%
“…GABA concentrations measured with proton magnetic resonance spectroscopy were significantly elevated in the occipital cortex of depressed patients following ECT. [26] The increased levels of GABA in association with ECT may explain its antidepressant actions. In addition, increased GABA concentrations in the occipital cortex were also found during treatment of MDD with serotonergic antidepressants.…”
Section: Gaba In Mdsmentioning
confidence: 99%